2006
DOI: 10.1111/j.1752-1688.2006.tb04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Watershed Planning in Washington State

Abstract: This paper draws on interviews with Washington State Watershed Planning Leads (Planning Leads) and interactions with local watershed planning units to identify factors that may influence the inclusion of climate change in watershed planning efforts in Washington State. These factors include the interest of individual planning unit members in climate change; Planning Lead familiarity with climate impacts; the influence of trust, leadership, and “genetic knowledge” on planning units; and perceptions of strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…On the other hand, in the recreation sector, a lack of regional organization for fishing guides may limit the diffusion of science-based information on climate change impacts throughout the community. Given the importance of early understanding of climate change impacts at the local-level in giving communities time to develop the capacity to adapt (Whitely Binder, 2006), this may lessen their capacity to respond and adjust, for example, through planning to shift some of their activities to different locations or times of year or guiding their efforts to influence proposed legislation regarding permitting and zoning of guided fishing in the state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in the recreation sector, a lack of regional organization for fishing guides may limit the diffusion of science-based information on climate change impacts throughout the community. Given the importance of early understanding of climate change impacts at the local-level in giving communities time to develop the capacity to adapt (Whitely Binder, 2006), this may lessen their capacity to respond and adjust, for example, through planning to shift some of their activities to different locations or times of year or guiding their efforts to influence proposed legislation regarding permitting and zoning of guided fishing in the state.…”
Section: Resultsmentioning
confidence: 99%
“…The Council's main focus areas are fish and wildlife habitat, water quantity and quality, recreation, and human habitat, but because it includes a broad range of users, it has the potential to provide an institutional structure that could be used as a forum to negotiate changes to the management of water resources under changing conditions (Six, 2007). These types of existing stakeholder networks have been found to be important for dissemination of climate information, and this type of locally based watershed planning may be valuable for building adaptive capacity in managing climate change impacts (Ziervogel and Downing, 2004;Whitely Binder, 2006). Although the capacity to adapt to changing conditions is considered a benefit of this type of collaborative resource management, the level of conflict among competing water uses would likely play an important role in determining whether the Council would serve to strengthen the response capacity of these user groups, with adaptability considered to be lower where there is a high level of conflict (Miles et al, 2000;Heikkila and Gerlak, 2005).…”
Section: Response Capacity: Municipal Watermentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that temperature was also a critical factor for runoff generation: for the Spokane River basin, a 20% precipitation increase could result in a streamflow increase of 48% if the temperature is 1°C lower but only a 4% increase if the temperature is 1Ð8°C higher than the long-term mean. Binder (2006) drew on interviews with Washington State Watershed Planning Leads and interactions with local watershed planning units to identity factors that may influence the inclusion of climate change in watershed planning efforts in Washington State. These factors included the interest of individual planning unit members on climate change; Planning Lead familiarity with climate impacts; the influence of trust, leadership, and 'genetic knowledge' on planning unit; and perceptions of strategic gain.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, esses métodos são incapazes de representar as características locais (Dibike & Coulibaly, 2005). Binder (2006) recomenda detalhar os cenários disponíveis das mudanças climáticas para a escala de bacia hidrográfi ca, utilizando-se, também, modelos hidrológicos, a fi m de se estudar impactos das mudanças nos recursos hídricos. Essa redução de escala dinâmica inclui o aninhamento de um modelo de circulação regional a uma resolução mais grosseira de um modelo de circulação global.…”
Section: Introductionunclassified